Viral biocontrol: grand experiments in disease emergence and evolution - Di Giallonardo, Francesca (Trends Microbiol, 2014)
Although viral emergence is commonly associated with cross-species transmission, the processes and determinants of viral evolution in a novel host environment are poorly understood. We address key questions in virus emergence and evolution using data generated from two unique natural experiments: the deliberate release of myxoma virus (MYXV) and rabbit hemorrhagic disease virus (RHDV) as biological control (biocontrol) agents against the European rabbit in Australia, and which have been of enormous benefit to Australia’s ecosystem and agricultural industries. Notably, although virulence evolution in MYXV and RHDV followed different trajectories, a strongly parallel evolutionary process was observed in Australia and Europe. These biocontrol agents were also characterised by a lack of transmission to non-target host species, suggesting that there are major barriers to successful emergence.